The infrastructure bias in Vietnamese climate change adaptation - Lily Salloum Lindegaard (Danish Institute for International Studies (DIIS), 2013)
This working paper examines the climate change adaptation strategies of meso-level, or mid-level, government institutions in central Vietnam. It reveals a significant bias towards infrastructure over so-called 'soft' solutions. The main drivers behind this bias - a techno - cratic desire for visible solutions, a need to secure socio-economic development and aspects of the state apparatus itself - are explored and explained using data from interviews with government officials. Ultimately, the paper describes the key challenges this infrastructure bias creates for climate change adaptation, socio-economic development and local people's relations with their environment
Keywords: 300